Perancangan Sistem Informasi Pendataan Korban Bencana Alam Dan Bencana Sosial Di Dinas Sosial Kota Palembang Berbasis Website - Dedi Haryanto; Zulhipni Reno Saputra Elsi; Meliana Winda Perdana; Jimmei Jimmei (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
Handling events that occur, by evacuating, meeting needs, protection are things that must be done by the government and local governments and emergency response. The Palembang City Social Service is a government institution that has many fields, one of which is PJS (Social Protection and Security) which has a Head of Social Protection for Natural and Social Disaster Victims (PSKBA / BS). In collecting data on victims of Natural and Social Disasters, the Social Service of Palembang City has used a computer in its data collection, but the data collection is still using MS Excel where the data can be lost at any time. Therefore, this study aims to design a web-based system that helps in collecting data on victims of natural and social disasters that can minimize data loss. In building information system software, the author uses an object-oriented method with a waterfall approach which consists of several stages, namely Requirements Analysis (requirements), System Design (design), System Implementation (implementation), System Testing (testing), and System Maintenance (maintenance). . The design of the Information System for Data Collection of Victims of Natural Disasters and Social Disasters at the Social Service of Palembang City is a system design process that can later be implemented in programming language which aims to make it easier for officers or admins to collect data and also recap reports quickly and accurately. The design of this system is based on the problems that exist at this time where the data collection process is still using Ms Excel which is considered to be still ineffective. The currently designed system is equipped with a menu of disaster data, command posts, victim data, officers, assistance, and a recap menu. Where these menus can support the system to be maximized and in accordance with user needs.Keywords : Information System, Waterfall, WebÂ